Design and manufacturing of a thermoplastic composite fan blade: Process-induced deformation simulation with fiber-draping analysis and its experimental validation - Thuan, Ho-Nguyen-Tan; Jeon, Min-Hyeok; Jung, Kyung Seok; Yu, Jaesang; Kim, Minkook; Yoon, Soon Ho (Pergamon Press Ltd., 2024)
This paper presents an efficient methodology for designing and manufacturing a thermoplastic composite (TPC) fan blade. The structural thickness distribution is employed to define the lamination ply layup on middle shell mesh of the fan blade. Ply shape codes with high manufacturability are constructed using the marching square algorithm. A numerical analysis of fiber-draping is proposed to predict the distortion of fiber orientations due to shell curvatures and twisted angles. These fiber orientations are employed to simulate the processinduced deformation resulting from thermal anisotropy in the TPC fan blade. The simulated process-induced deformations accounting for the fiber-draping analysis closely align with experimental results.